古巴学习者汉语单字调偏误的声学分析 - Alejandro, Vera Trujillo Leonardo (Confucius Institute Universitas Sebelas Maret, 2025)
Drawing on the theoretical framework of experimental phonetics, this study investigates the development of Mandarin tone acquisition among Cuban learners at beginner, intermediate, and advanced proficiency levels. Through a combination of acoustic analysis and perceptual assessment, the research examines tone production and error patterns with respect to pitch range, tonal contour, and fundamental frequency movement. Data were selected from a corpus of Cuban learners of Chinese, yielding a sample of 10 representative participants: 5 beginners, 3 intermediate learners, and 2 advanced learners. Each participant read 99 monosyllabic syllables, with the neutral tone excluded. Fundamental frequency data were obtained using Praat, and four experienced raters conducted perceptual evaluations. The findings indicate a general upward trend in tonal competence as proficiency increases, with all four Mandarin tones showing relatively high accuracy overall. The relative difficulty of the tones is ordered from Tone 1 to Tone 2, Tone 4, and Tone 3, suggesting that basic tonal awareness is already present at the initial learning stage. The results further reveal that tone acquisition follows a non-linear developmental trajectory: beginner learners tend to overproduce tonal features, intermediate learners prioritise fluency over accuracy, and advanced learners demonstrate a more balanced, though not fully native-like, performance. Persistent confusion between Tone 2 and Tone 3 emerges as the most salient error type. Moreover, learners consistently exhibit lower pitch registers across levels, likely influenced by their first language. Tonal stability improves steadily with proficiency, indicating increasing control over tone production.